Teaching activity, curriculum and fields of influence in classroom - Laura Cristina Vieira Pizzi; Wanessa Lopes de Melo (Universidade Federal de Santa Maria, 2013)
The purpose of this article is to analyse teaching activity, from the perspective of Activity Clinic of Yves Clot (2010), focusing on the curriculum developed in classroom, considering the conditions of its realization, requirements, contingencies and crossings in everyday life. To approach the complexity of the curriculum we use the Simple Self-confrontation technique, which uses the filming as a primary means of data collection. The teacher in this study worked in 2nd grade in a public Municipal Elementary School of Maceió/AL, located on the outskirts. The prescriptive character of curriculum policy was not determinant in curricular activity of this teacher, compared to other subjective factors and other content and subjects that readjusted the curriculum, printing new developments and implications.